PENINGKATAN KEMAMPUAN MEMBILANG 1 – 20 MELALUI PERMAINAN PUZZLE PADA ANAK KELOMPOK B DI TK TUNAS RIMBA 1 SAMARINDA TAHUN PEMBELAJARAN 2016/2017 - Umi - Sudarwati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2018)
The background of this research is the importance of the ability to count for early childhood, to be able to hone the cognitive development of children, especially in the field of mathematics. So the need for learning methods that can meet the needs of children. The formulation of the problem in this research is how to improve the ability of spelled out 1-20 through the puzzle game in the children group B TK Tunas Rimba 1 Samarinda. The purpose of this study is to find out how the puzzle game can improve the ability to count 1-20 children. This type of research is a classroom action research. Research subjects were teachers and children group B TK Tunas Rimba 1 Samarinda. The classroom teacher acts as the executing subject of action and child group B TK Tunas Rimba 1 Samarinda as the subject of the recipient of the action of 15 people. The object of this research is Improved 1-20 through the ability of the game puzzle. Data collection techniques use observation techniques. The research instrument used is observation sheet and documentation in the form of portfolio observation sheet and checklist. Data analysis used in this research is descriptive qualitative with percentage. The result of data analysis is known that the ability of children to be 1-20 through puzzle game in cycle I is got average value 44 with criteria less once, then increase in cycle II by 43%, obtained by average value 63 with enough criteria. and on the third cycle increased by 19%, obtained an average value of 75 with good criteria. So we can get 1-20 children from cycle I to cycle III 70%. The conclusion of this research result that through puzzle game can improve the ability of counted 1-20 early childhood, especially child group B TK Tunas Rimba 1 Samarinda Year Learning 2016/2017.